Perancangan Sistem Informasi dan Pendataan Perangkat Pelaksanaan Skripsi atau Tugas Akhir di Jurusan Teknik Elektro Universitas Negeri Padang - Syulaiman Agazali; Dwiprima Elvanny Myori (JTEV (Jurnal Teknik Elektro dan Vokasional), 2020)
The design of thesis data collection system aims to record the title of the thesis that has been made by students and also to find out the number of students who are guided by each lecturer, and to avoid working on the same thesis title between one student and another. The taking of the same title mostly occurs in students who are in the process of carrying out research. This happens because students are less active in finding out the titles that have been discussed and also because the facilities to access titles that have been registered in the Electrical Engineering Department of UNP do not yet exist. In this data collection system, there is information on titles that have been registered in the Department of Electrical Engineering, UNP, and also information on the list of names of students under the guidance of lecturers and the titles of theses that are in progress. The method of making this data collection system uses 2 steps. The first is creating a database using XAMPP software, and then making a web database using visual studio code. After testing the system that has been designed, it can be concluded that the system has been running as planned. With this data collection system, it can be seen that there will no longer be the same student title and also information on the number of students who are mentored by lecturers.